Effect of short-term fasting on urinary excretion of primary lipid peroxidation products and on markers of oxidative DNA damage in healthy women - Lee, Kyoung-Ho; Bartsch, Helmut; Nair, Jagadeesan; Yoo, Dong-Ho; Hong, Yun-Chul; Cho, Soo-Hun; Kang, Daehee (Carcinogenesis, 2006)
Abstract. The goal of this study was to determine whether short-term fasting changes in urinary biomarkers related to oxidative stress: malondialdehyde (MDA), 8
Gesehen am 23.11.2020